Pemberdayaan Masyarakat Sakinah dalam Upaya Pemberantasan Buta Huruf Al-Qur’an di Kampung Sakinah: Empowerment of The Sakinah Community In Efforts to Eradicate Al-Qur'an Illumination in Sakinah Village - Rivo Alfarizi Kurniawan; Neny Ismiyanti; Qutsiati Rofiqoh; Ferry Irawan; Fikria Tahta A.; Khoiriyatul Musyarofa; Nuril Azrina; Diana Fitri K.R.; Retno Bulan A.S.; Sayyidatur Risqiyah; Abdullah Ubhih Y; Azza Myla U.S.; Nuva Nur K.; Achmad Robich B.; Tirza Hayatur R.; Feliya Dwi T.; Alfiyanti Solehani; Putri Handika D.A.; Muhammad Muhib Alwi (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2022)
Seeing the high level of Qur'an illiteracy survivors in the village of Sakinah and the very limited number of teaching staff to read the Qur'an, it is necessary to have a Qur'an illiteracy eradication program to support government programs in reducing the number of survivors. illiteracy of the Koran. The purpose of this research is to know the empowerment of the people of the sakinah village in an effort to eradicate illiteracy in the Qur'an in the sakinah village. The method used is descriptive qualitative method. The results of the service were obtained by several activities to eradicate al-Qur'an illiteracy in the sakinah village, namely socialization activities on the importance of learning the Qur'an, debriefing the knowledge of tajwid and makhorijul literacy, community empowerment in eradicating illiteracy in the Qur'an and reading competitions. - Quran. The activities carried out run smoothly and well, this can be seen from the enthusiasm of the participants of Al-Qur'an illiterate survivors who continue to increase in participating in the activities carried out. Another result of the activities carried out was getting teachers to teach the Qur'an taken directly from the people of the Sakinah village. To maintain the continuity of the program implemented, students collaborate and coordinate with the KUA team in Tanggul sub-district. Melihat tingkat penyintas buta huruf al-qur’an di kampung sakinah yang cukup tinggi serta jumlah tenaga mengajar membaca al-qur’an yang sangat terbatas, maka diperlukan adanya program pemberantasan buta huruf al-qur’an guna mendukung program pemerintah dalam menekan jumlah penyintas buta huruf al-qur’an. Adapun tujuan dalam penelitian ini yaitu mengetahui pemberdayaan masyarakat kampung sakinah dalam upaya memberantas buta huruf al-qur’an di kampung Sakinah. Metode yang digunakan yakni metode kualitatif deskriptif. Hasil pengabdian diperoleh beberapa kegiatan guna memberantas buta huruf al-qur’an di kampung Sakinah yakni kegiatan sosilaisasi pentingnya belajar al-qur’an, pembekalan ilmu tajwid dan makhorijul huruf, pemberdayaan masyarakat dalam memberantas buta huruf al-qur’an serta lomba baca al-qur’an. Kegiatan yang dilakukan berjalan dengan lancar dan baik, hal tersebut terlihat dari antusiasme peserta penyintas buta huruf al-qur’an yang terus meningkat dalam mengikuti kegiatan yang dilakukan. Hasil lain dari kegiatan yang dilakukan yakni mendapatkan guru mengajar alqur’an yang diambil langsung dari masyarakat kampung sakinah. Untuk menjaga keberlanjutan program yang dilaksanakan, mahasiswa melakukan kolaborasi dan koordinasi bersama tim KUA Kecamatan Tanggul.